Exploring Pre-Service Teacher Professional Learning on Their Preparedness for Teaching Practicum - Moh. Rif’attullah; Ciptaningrum, Dyah Setyowati (PT FORMOSA CENDEKIA GLOBAL, 2024)
The teaching practicum is essential in pre-service teacher education, allowing aspiring teachers to apply theoretical knowledge in real classrooms. It helps them to develop practical skills, build communication abilities, and connect with clients, colleagues, and mentors. This study investigates pre-service teachers' perceptions of their readiness for teaching practicums, the influencing factors, and the contribution of professional learning programs on their preparedness. Using a mixed-method approach with an explanatory sequential design, the research was conducted in Metro City, Lampung. Data were collected through a close-ended questionnaire from 80 pre-service teachers and semi-structured interviews with 9 pre-service teachers who were ready as the volunteers. Descriptive statistics and qualitative analysis were used to analyze the data. Results indicated that professional learning programs significantly enhance preparedness in pedagogical training, content knowledge, classroom management, understanding diverse student needs, and technology integration. These programs boost confidence, competence, and the ability to create effective learning environments. Informal learning, such as roles as teaching assistants and using social media, also contributes significantly to innovative teaching. Integrating formal and informal learning experiences is crucial for the holistic development of pre-service teachers